Corporate Culture as A Determinant of The Prosperity of a Business Entity - Olga PONISCIAKOVA; Zuzana ROSNEROVA; Eva KICOVA (Communications of International Proceedings, 2023)
The concept of corporate culture is mentioned more and more in connection with the efficiency and prosperity of economic entities. First and foremost, everyone cares about customer satisfaction, which is often reflected in the company culture. If it is dysfunctional, it shows in the behaviour of individual employees. An unhealthy, weak corporate culture needs to be changed, as sooner or later it can affect financial results. A healthy corporate culture promotes values related to employee and customer satisfaction. The orientation is toward compliance with moral and ethical principles, maximum customer satisfaction, and team cooperation. In our contribution, we focus on the significance of the corporate culture of an economic entity operating in the field of services in Slovakia. We were interested in how the corporate culture works here and how the employees view its functioning. We have set as our main goal the analysis of the corporate culture of an economic entity operating in the field of services in Slovakia and the formulation of proposals and recommendations for strengthening the corporate culture of this entity. We set sub-goals for the main goal: to apply the quantitative inquiry method. On the basis of a questionnaire survey, we clarified the employees' view of the operation and the current situation in the company in the context of the company culture.
Keywords: : culture; organization; company culture; company; employees; typologies of company culture; values; and norms.